Genome-wide identification and analysis of the invertase gene family in tobacco (Nicotiana tabacum) reveals NtNINV10 participating the sugar metabolism - Cheng, Lingtong; Jin, Jingjing; He, Xinxi; Luo, Zhaopeng; Wang, Zhong; Yang, Jun; Xu, Xin (Frontiers in Plant Science, 2023)
Sucrose (Suc) is directly associated with plant growth and development as well as tolerance to various stresses. Invertase (INV) enzymes played important role in sucrose metabolism by irreversibly catalyzing Suc degradation. However, genome-wide identification and function of individual members of the INV gene family in Nicotiana tabacum have not been conducted. In this report, 36 non-redundant NtINV family members were identified in Nicotiana tabacum including 20 alkaline/neutral INV genes (NtNINV1-20), 4 vacuolar INV genes (NtVINV1-4), and 12 cell wall INV isoforms (NtCWINV1-12). A comprehensive analysis based on the biochemical characteristics, the exon-intron structures, the chromosomal location and the evolutionary analysis revealed the conservation and the divergence of NtINVs. For the evolution of the NtINV gene, fragment duplication and purification selection were major factors. Besides, our analysis revealed that NtINV could be regulated by miRNAs and cis-regulatory elements of transcription factors associated with multiple stress responses. In addition, 3D structure analysis has provided evidence for the differentiation between the NINV and VINV. The expression patterns in diverse tissues and under various stresses were investigated, and qRT-PCR experiments were conducted to confirm the expression patterns. Results revealed that changes in NtNINV10 expression level were induced by leaf development, drought and salinity stresses. Further examination revealed that the NtNINV10-GFP fusion protein was located in the cell membrane. Furthermore, inhibition of the expression of NtNINV10 gene decreased the glucose and fructose in tobacco leaves. Overall, we have identified possible NtINV genes functioned in leaf development and tolerance to environmental stresses in tobacco. These findings provide a better understanding of the NtINV gene family and establish the basis for future research.